People with chronic obstructive pulmonary disease exacerbations prefer early discharge, then treatment at home. (19th February 2019) - Cook, Rob; Thomas, Vaughan; Martin, Rosie
The study: Home treatment of COPD exacerbation selected by DECAF score: a non-inferiority, randomised controlled trial and economic evaluation Echevarria C, Gray J, Hartley T, Miller J, Simpson AJ, Gibson GJ, Bourke SC Published on 24 April 2018 Thorax 2018;73:713-22 This project was funded by the National Institute for Health Research—Research for Patient Benefit Programme (project number PB-PG-0213-30105). To read the full NIHR Signal, go to: https://discover.dc.nihr.ac.uk/content/signal-000691/hospital-at-home-treatment-for-copd-flare-ups